Kualitas Pelayanan Penjualan Sepeda Motor Pada CV. Akai Jaya Sentral Yamaha Palu - Fachrul Reza (Jurnal ADMINISTRATOR, 2021)
The aim of this research to know the quality of sales service of CV. Akai jaya Sentral Yamaha Palu. The informant of this research consists of chief of store and consumer of CV. Akai jaya Sentral yamaha Palu. The data of this research consists of primary and secondary data which is obtain from the result of interview of consumer. The data analysis of this research is qualitative.The result of this research show that the quality that seen from physical evidence of CV. Akai Jaya Sentral Yamaha Palu is good enough but need to expand the parking area. The quality of services that seen from reliability in CV. Akai Jaya Sentral Yamaha Palu is good. The quality of services that seen from guarantee of CV. Akai Jaya Sentral Yamaha Palu is not good yet. And the last, the quality of services that seen from empathy of CV. Akai Jaya Sentral Yamaha Palu is already good.